The Role of Mean Platelet Volume in the Exacerbation of Chronic Obstructive Pulmonary Disease - حجازية مالك; الحسين فراس; فتاحي ديمة (Latakia University Journal -Medical Sciences Series, 2020)
Background: Studies have supported the correlation between mean platelet volume and COPD. However, there are limited data on the relationship between COPD exacerbation and mean platelet volume. Aim: This study was aimed to evaluate the mean platelet volume trend in patients with COPD exacerbation. Materials and Methods: This was a prospective study in which 80 patients with acute COPD exacerbation were enrolled at Tishreen University Hospital, Lattakia during the period between 2020 - 2019. The levels of mean platelet volume, C-reactive protein, complete blood count, and percent of predicted FEV1 were measured in subjects at admission (exacerbation period) and after 3 months (stable period). Results: Subjects in the exacerbation period had significantly higher levels of C-reactive protein (P<0.0001), white blood cell count (P<0.0001) and percentage of neutrophils (P<0.0001) and lower percent-of-predicted FEV1 than in the stable period (P<0.0001). Mean platelet volume levels were significantly decreased in the exacerbation period (P<0.0001). Mean platelet volume levels correlated significantly with increase of C-reactive protein level in the exacerbation period (r = -0.342, p<0.001) and in the stable period (r = -0.168, p=0.0347). Conclusion: Mean platelet volume may be an inflammatory marker in exacerbation of COPD.